Relationship between Masculinity and Femininity Depicted in Paulo Coelho's Brida (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This research is about gender studies in the tradition of the sun and the tradition of the moon as depicted in Paulo Coelho’s Brida. Both traditions are symbols of masculinity and femininity in witchcrafts. Therefore, besides utilising the concept of gender, this study also applies semiotics approach to comprehend the symbols in the narration. This research is qualitative by using descriptive-analytic since the data collected from the text then analyse them based on the meaning of symbols in gender perspective. As the result, this research finds that masculinity and femininity in witchcrafts shape their personality in society.